Polymorphs and Hydrates of Acyclovir - LUTKER, KATIE M. (2010)
Acyclovir (ACV) has been commonly used as an antiviral for decades. Although the crystal structure of the commercial form, a 3:2 ACV/water solvate, has been known since 1980s, investigation into the structure of anhydrous ACV has been limited. Here, we report the characterization of four anhydrous forms of ACV and a new hydrate in addition to the known hydrate. Two of the anhydrous forms appear as small needles and are stable to air exposure, whereas the third form is morphologically similar but quickly absorbs water from the atmosphere and converts back to the commercial form. The high-temperature modification is achieved by heating anhydrous form I above 180°C. The crystal structures of anhydrous form I and a novel hydrate are reported for the first time.